2012
DOI: 10.3102/0002831211415250
|View full text |Cite
|
Sign up to set email alerts
|

Switching Schools

Abstract: Youth who switch schools are more likely to demonstrate a wide array of negative behavioral and educational outcomes, including dropping out of high school. However, whether switching schools actually puts youth at risk for dropout is uncertain, since youth who switch schools are similar to dropouts in their levels of prior school achievement and engagement, which suggests that switching schools may be part of the same long-term developmental process of disengagement that leads to dropping out. Using data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 62 publications
1
49
0
Order By: Relevance
“…Some of these, such as low grades and low attachment to school, could have prompted their parents to move them to different schools (cf. Gasper et al, 2012; Rumberger & Larson, 1998). Others, such as inconsistent parental discipline, may have been associated with the general family disruption that precedes moves (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these, such as low grades and low attachment to school, could have prompted their parents to move them to different schools (cf. Gasper et al, 2012; Rumberger & Larson, 1998). Others, such as inconsistent parental discipline, may have been associated with the general family disruption that precedes moves (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that adolescents who move are themselves more involved in delinquency and substance use (Haynie & South, 2005; Hoffman & Johnson, 1998), have more psychological difficulties (Gilman, Kawachi, Fitzmaurice, Buka, & 2003; Haynie, South, & Bose, 2006a), and have lower grades, test scores, educational expectations, and educational attainment (Pribesh & Downey, 1999; Rumberger and Larson, 1998; South, Haynie, & Bose, 2007; Sutton, Muller, & Langenkamp, 2013, Swanson & Schneider, 1999). Yet three studies that specifically addressed selection bias via within-individual analyses and propensity score models found that under those methods school and residential moves were not associated with adolescents’ own delinquency and substance use (Gasper et al, 2010; Porter & Vogel, 2014), and school moves were only weakly associated with school dropout (Gasper et al, 2012). In addition, data from the experimental Moving to Opportunities study and from the quasi-experimental Yonkers Project suggest that residential moves have mixed effects on youths’ academic, psychological, and behavioral problems (Fauth, Leventhal, & Brooks-Gunn, 2005; Gennetian et al, 2012).…”
Section: Selection In the Association Of Moving With Friendshipsmentioning
confidence: 99%
“…Children of military parents are three times more likely to change schools, averaging around six to nine moves during their kindergarten to 12th grade education (U. S. Department of Education 2012). These abrupt changes have been found to put strains on existing friendships, create gaps in learning and education, and result in added stress from adjusting to new surroundings (Gasper et al 2012).…”
Section: Adverse Outcomes For Children Of Military Familiesmentioning
confidence: 99%
“…Mobility has been most commonly investigated in previous work using survey data collected in longitudinal studies (Freeman, 2005; Gasper et al , 2012; Kan, 2007). Most frequently, residential histories are collected from respondents to identify the timing, number, and distance of moves.…”
Section: Datamentioning
confidence: 99%